How to Improve the Results of Peripheral Nerve Surgery - Millesi, Hanno; Schmidhammer, Robert (Acta Neurochirurgica Supplement, 2007)
All over the world research is going on to improve the outcome of the treatment of peripheral nerve lesions. Questions over questions arise. Is the autologeous nerve grafting still the golden standard in bridging defects? Have alternative techniques to overcome defects reached a level to replace autografting? To which length are they effective? What is the role of allografting? Are there still indications for vascularized nerve grafts? What can be expected from end to side coaptation? Does it exist at all? Under what conditions useful recoveries can be achieved? Are there new developments in physical medicine and physiotherapy? Can the quality of recovery be influenced by surgery on muscles to provide a better equilibrium of forces? To what extent cerebral plasticity may be exploited to improve functional results? The contributions in this book give answers to all of these questions.